Credit-Supply Shocks and Firm Productivity in Italy - Dorr, Sebastian (IMF Working Papers; Working Paper ;, 2017)
The Italian economy has been struggling with low productivity growth and bank balance sheet strains. This paper examines the implications for firm productivity of adverse shocks to bank lending in Italy, using a novel identification scheme and loan-level data on syndicated lending. We exploit the heterogeneous loan exposure of Italian banks to foreign borrowers in distress, and find that a negative shock to bank credit supply reduces firms' loan growth, investment, capital-to-labor ratio, and productivity. The transmission from changes in credit supply to firm productivity relates to labor market rigidities, which delay or distort the adjustment of firms' desired labor and capital allocations, and thereby reduce firms' productivity. Effects are stronger for firms with higher capital intensity and external financial dependence.